Agrarian Reform, Institutional Fragmentation and Land Justice in Indonesia - Sulfian, A. Sultan; Ansar , Lukman; Firdaus; Aboalela, Nahi Hashim Fathi; Albarahmeh, Mohammad Yusuf Musa (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This article examines the acceleration of agrarian reform in Indonesia as a strategic instrument for achieving justice in land ownership, with a focus on the implementation of Presidential Regulation No. 62 of 2023. Despite successive reform initiatives, persistent structural inequalities in land tenure continue to generate agrarian conflicts, social exclusion, and unequal economic access. Using a normative legal approach based on statutory, conceptual, and legal-theoretical analysis, the study evaluates the regulatory framework and its implementation within Indonesia’s land governance system. The findings indicate that Presidential Regulation No. 62 strengthens the institutional framework for agrarian reform, yet implementation remains constrained by overlapping sectoral regulations, fragmented land administration, incomplete land data, and limited institutional capacity. These barriers hinder equitable land redistribution and legal certainty for communities. The study argues that agrarian reform should be understood not merely as a redistributive policy, but as a transformative mechanism for promoting social justice, economic inclusion, and sustainable rural development. Effective reform thus requires regulatory harmonization, institutional strengthening, transparent monitoring, and meaningful community participation, providing insights for both legal scholarship and policy practice.